2016
DOI: 10.1139/cjps-2015-0124
|View full text |Cite
|
Sign up to set email alerts
|

Halosulfuron tankmixes applied preplant incorporated for weed control in white bean (Phaseolus vulgaris L.)

Abstract: Six field experiments were conducted over a two-year period (2013 and 2014) to evaluate the tolerance of white bean and spectrum of weeds controlled with halosulfuron applied preplant incorporated (PPI) alone or tankmixed with trifluralin, pendimethalin, EPTC, dimethenamid-P, or S-metolachlor. Halosulfuron applied alone or in tankmix with trifluralin, pendimethalin, EPTC, dimethenamid-P, or S-metolachlor caused 2% or less visible injury 1 and 4 weeks after emergence (WAE). Halosulfuron applied PPI controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 29 publications
1
23
0
1
Order By: Relevance
“…O herbicida halosulfuron apresenta registro, no Brasil, para controle de Cyperus sp., na dose de 112,5 g ha -1 i.a., na cultura da cana-de-açúcar (Rodrigues e Almeida, 2011). A aplicação deste herbicida, isolado ou em associações, também é relatada como eficaz no controle de outras plantas, tais como Erechtites hieraciifolia (Atkinson et al, 2014), Armoracia rusticana (Johanning et al, 2016), Chenopodium album, Amaranthus retroflexus e Ambrosia artemissifolia (Li et al, 2016).…”
Section: Resultsunclassified
“…O herbicida halosulfuron apresenta registro, no Brasil, para controle de Cyperus sp., na dose de 112,5 g ha -1 i.a., na cultura da cana-de-açúcar (Rodrigues e Almeida, 2011). A aplicação deste herbicida, isolado ou em associações, também é relatada como eficaz no controle de outras plantas, tais como Erechtites hieraciifolia (Atkinson et al, 2014), Armoracia rusticana (Johanning et al, 2016), Chenopodium album, Amaranthus retroflexus e Ambrosia artemissifolia (Li et al, 2016).…”
Section: Resultsunclassified
“…The direct effect of halosulfuron applied PPI decreased the density of common lambsquarters and wild mustard more than 70% and green foxtail more than 30% (Figure 1). This direct efficacy would provide essential yield protection in white bean [7]. But in addition, the indirect effect, the delayed emergence of lambsquarters and wild mustard would provide additional and possibly substantive additional yield protection.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Chikoye et al [4] reported that a 2 week delay in common ragweed emergence resulted in significantly less weed seed production [4]. When applied PRE, Li et al [6] [7] found that halosulfuron reduced the dry weight of common lambsquaters and wild mustard by more than 99% compared to the weedy control suggesting that the weeds that do emerge late and survive would likely not produce substantive amounts of seed [6] [7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations